Method of relative forecast of electronic equipment reliability by the level of low-frequency noise - Kychak, V. M.; Mykhalevskyi, D. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
New method of prognostication electronic equipment forecast by the level of low-frequency noise is suggested. The characteristic feature of this method is the use of two channels for level of noise measurement. This allows to decrease considerably the level of systematic error, eliminate the influence of temperature characteristics and electromagnetic interference. The paper contains characteristics of the device, flow diagram and operation algorithm of work.